Analisis Uji Beda Dampak Pandemi Covid-19: Peran Struktur Modal Dan Kinerja Perusahaan - Mais, Rimi; Puspitasari , Marsih (STIE Indonesia Banking School, 2024)
This research aims to determine the effect of capital structure on the financial performance of finance companies listed on the Indonesia Stock Exchange for the 2017-2021 period before and during the Covid-19 pandemic. The variables used to measure capital structure are debt to equity ratio (DER), debt to asset ratio (DAR), equity to asset ratio (EAR) and long term debt to equity ratio (LTDE). Meanwhile, the variable used to measure the company's financial performance is the return on equity (ROE) profitability ratio. This research uses quantitative research methods, which are measured using panel data which is a combination of time series data (time-series) and cross-section data and processed using Eviews. The population of this research is companies listed on the Stock Exchange Indonesian Securities from 2017 to 2021. The sample was determined based on the purposive sampling method, with a total sample of 14 companies. The data used in this research is secondary data. The data collection technique uses the documentation method via the official IDX website: www.idx.co.id. Hypothesis testing uses panel data regression, t test, f test and coefficient test. Research results before the pandemic showed that DER had a negative effect on ROE, DAR had a positive effect on ROE, EAR had no effect and was not significant on ROE and the Long Term Debt to Equity Ratio had no effect on ROE. So when the Covid-19 pandemic occurred, research results showed that DER, DAR, EAR & LTDE had no effect on ROE, which means that financial performance is not solely determined by capital structure.